2009
DOI: 10.1186/1745-9974-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Classification of voluntary cough sound and airflow patterns for detecting abnormal pulmonary function

Abstract: Background: Involuntary cough is a classic symptom of many respiratory diseases. The act of coughing serves a variety of functions such as clearing the airways in response to respiratory irritants or aspiration of foreign materials. It has been pointed out that a cough results in substantial stresses on the body which makes voluntary cough a useful tool in physical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Publications from Korpas and coworkers have previously suggested that studying voluntary cough sounds known as tussophonography may be useful in diagnosing respiratory diseases [31] and recent work measuring voluntary cough sounds and flow measures found sound features may reflect pulmonary function abnormalities [51,52].…”
Section: Cough Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Publications from Korpas and coworkers have previously suggested that studying voluntary cough sounds known as tussophonography may be useful in diagnosing respiratory diseases [31] and recent work measuring voluntary cough sounds and flow measures found sound features may reflect pulmonary function abnormalities [51,52].…”
Section: Cough Qualitymentioning
confidence: 99%
“…Flow changes during a single voluntary cough (A) with the associated cough sound (B).Reproduced with permission from[51].…”
mentioning
confidence: 98%
“…The nature of the anomalous sounds varies between stationary events such as wheezes or rhonchus, to transient sounds such as crackles, both at fine and coarse scales. Of all lung sounds of interest for medical diagnosis, wheezes and crackles are the most studied components and are indicative of specific pathologies [3], [4]. Wheezes are generally louder than the underlying breathing sound with duration longer than 250ms and are usually signs of obstructive pulmonary diseases (such as asthma).…”
Section: Introductionmentioning
confidence: 99%
“…Here, abnormal spirometry is defined as less than the lower limit of normal (LLN) predicted by standard reference equations [1]. Cough airflow signals of 107 subjects (56 male, 51 female) were previously collected [2] from patients performing spirometry in a pulmonary function clinic. A variety of features were extracted from the airflow signal.…”
mentioning
confidence: 99%
“…Cough airflow signals of 107 subjects (56 male, 51 female) were previously collected [2] from patients performing spirometry in a pulmonary function clinic. A variety of features were extracted from the airflow signal.…”
mentioning
confidence: 99%